Repositioning the Service Worker: An Islamic Dawah Based Perspective - Muhammad Kashif (Proceeding Of The International Seminar and Conference on Global Issues, 2015)
Dawah as a religious practice is well known. However, how it can help organizations to relay differentiate on the basis of their workforce is unknown to business and management scholars. This concept paper aims to contribute to management knowledge by proposing a Dawah based perspective to brand the workforce for service organizations, operating particularly in Muslim countries such as Indonesia and Pakistan. The Quranic verses are interpreted (in a much more focused way) to extract a few key elements which can be used by organizations to train their workforce. The article also highlights how Muslim countries can collaborate with each other to practice Dawah at the workplace. Keywords: Dawah, ethics, Muslim, Islam